'When it comes to HIV, that's when you find out the genuinity of that love': The experience of disclosing a HIV+ status to an intimate partner. (July 2019) - Smith, Charlotte; Cook, Rachel; Rohleder, Poul
Despite a medical discourse of the 'normalisation' of HIV, it remains a highly stigmatising condition and makes the issue of disclosing one's HIV status particularly complex. This article reports on the experience of 18 people living with HIV in the United Kingdom of disclosing their HIV+ status in arguably their most important relationship, their intimate partnership. Five main themes arose: disclosure as the battlefield, preparing psychologically to disclose, disclosure as a test of the partner's love, disclosure as an opportunity for the partner to know them more deeply and the renegotiation of the relationship narrative.